2020
DOI: 10.1038/s41598-020-66723-1
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in human facial skin observed by ultraweak photon emission imaging and its correlation with biophysical properties of skin

Abstract: Oxidative stress is associated with skin ageing and disease in humans. However, it is difficult to evaluate the effects of oxidative stress on the skin in vivo using conventional invasive methods. in this study, we performed two-dimensional imaging of ultra-weak photon emission (Upe) generated by excited species in oxidative reaction to determine regional variations in oxidative stress in human facial skin and analysed the relationship between Upe intensity and biophysical properties in vivo. Upe imaging of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…Collectively, these findings suggest a relationship between UV light induced lipid peroxidation and wrinkle formation. Indeed, our previous study confirmed a relationship between oxidative stress and wrinkle formation in facial skin 23 . α-Linolenic acid accumulates in the body of mammals (carcass, adipose, and skin) and its major metabolic route is beta-oxidation.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Collectively, these findings suggest a relationship between UV light induced lipid peroxidation and wrinkle formation. Indeed, our previous study confirmed a relationship between oxidative stress and wrinkle formation in facial skin 23 . α-Linolenic acid accumulates in the body of mammals (carcass, adipose, and skin) and its major metabolic route is beta-oxidation.…”
Section: Discussionsupporting
confidence: 79%
“…Porphyrin 49 and melanin 50 in the skin are known to cause photosensitization reactions, and other chromophores such as bilirubin, NAD(P)H, trans -urocanic acid, and tryptophan have also been proposed as photosensitizers 51 . Our previous study reported a correlation of porphyrin with UPE 23 . UVA excites photosensitizers in the skin, which in turn oxidize biomolecules, thus resulting in the release of UPE from the skin surface.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Ultra-weak photon emission results from reactions involving ROS formed during oxidative metabolic processes [25,33,34]. Reactive oxygen species generated at low concentrations in cells act as signaling molecules that facilitate significant responses in plant cells such as controlling growth, development and helps in developing tolerance to environmental strains [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in hydrophobicity was expected as reduced levels of covalently bound lipids have been observed on forearm SC as well as of substrate and associated enzymes necessary for their attachment in photoaged skin sites. This could be the reason for the decline in the hydrophobicity in the aged nasolabial areas as these facial sites are those recently reported to have the highest levels of oxidative stress [ 17 ]. The ageing‐related decreases in CE rigidity were consistent across all four sites (Fig.…”
mentioning
confidence: 99%